2010
DOI: 10.1590/s0102-86502010000400013
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy and mechanical resistence of the colonics anastomosis in rats with peritonitis

Abstract: Purpose:To analyze the effects of hyperbaric oxygen therapy (HBO) on the mechanical resistance of anastomosis performed in rats' distal colon presenting peritonitis induced by ligature and cecal punction using the Total Energy Rupture biomechanical test (ETR). Methods: It was used 45 rats divided into three groups of 15 animals each. In Control Group (CG), it was performed anastomosis in distal colon without peritonitis. In Peritonitis Group (PG), it was performed anastomosis six hours after the induction of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Other two studies corroborate our findings of no significant differences in ischemic necrosis and reepithelization 8,16 .…”
Section: ■ Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other two studies corroborate our findings of no significant differences in ischemic necrosis and reepithelization 8,16 .…”
Section: ■ Discussionsupporting
confidence: 92%
“…Previous studies had different results with statistically significant increase in HBOT groups in neovascularization 16,27,30 , and in collagen deposition 8 .…”
Section: ■ Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They showed that delay in granulation tissue formation and fibroblast proliferation significantly influenced the therapy groups. Rocha et al 57 showed that hyperbaric oxygen therapy did not alter the mechanical resistance of anastomosis in distal colon of rats in the presence of peritonitis. Murray 33 found that impairment due to an increase in the collagen and protein synthesis in the early postoperative colon surgery after radiation returned to the normal levels on the fourth month.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha et al 13 demonstrated that peritonitis made the total bursting energy values decrease significantly on the fourth day after performing anastomosis in rats' distal colon. De Hing et al 14 evidenced that peritonitis decreased the anastomosis' mechanical resistance on the third post-operatory day, returning to normality on the fifth day.…”
Section: Discussionmentioning
confidence: 99%